Co-development of a Web-based hub (eSocial-hub) to combat social isolation and loneliness in Francophone and Anglophone seniors in linguistic minority context (Quebec, Manitoba, and New Brunswick): Protocol for a mixed methods interventional study - Beogo, Irissa; Ramdé, Jean; Nguemeleu Tchouaket, Eric; Sia, Drissa; Bationo, Nenila Jean-Claude; Collin, Stéphanie; Anne, Abdoulaye; Gagnon, Marie-Pierre (JMIR Research Protocols, 2021)
Background: The first wave of the COVID-19 pandemic has severely hit Canadian nursing facilities (81% of deaths). To this toll, public health measures (eg, visitation restriction) have subsequently deepened the social isolation and loneliness of residents in nursing facilities (NFs), especially those in linguistic minority settings: Anglophone institutions in Quebec and Francophone institutions outside Quebec. However, very few COVID-19 initiatives targeting these populations specifically have been documented. Given the limited number of NFs serving linguistic minorities in Canadian populations, families and loved ones often live far from these facilities, sometimes even in other provinces. This context places the digital solutions as particularly relevant for the present COVID-19 pandemic as well as in the post–COVID-19 era. Objective: This project aims to co-develop a virtual community of practice through a web-based platform (eSocial-hub) to combat social isolation and loneliness among the older people in linguistic minority settings in Canada. Methods: An interventional study using a sequential mixed methods design will be conducted. Four purposely selected NFs will be included, 2 among facilities in Manitoba and 2 in New Brunswick; and 2 Anglophone NFs in Quebec will serve as knowledge users. The development of eSocial-hub will include an experimental 4-month phase involving the following end users: (1) older people (n=3 per NF), (2) families of the participating older people (n=3 per NF), and (3) frontline staff (nurse and health care aid; n=2 per NF). Results: Activities and solutions aiming at reducing social isolation and loneliness will be implemented and then evaluated with the project stakeholders, and the best practices generated. The assessment will be conducted using indicators derived from the 5 domains of the Consolidated Framework for Implementation Research. The project will be led by an interdisciplinary team and will involve a multisectoral partnership. Conclusions: The project will develop a promising and generalizable solution that uses virtual technology to help reduce social isolation and loneliness among the older people.

Promoting the health and well-being of English-speaking Seniors in Quebec. A community model (infographic) - Community Health And Social Services Network/Réseau communautaire de santé et de services sociaux (2019)
fs-ref-orig: Community Health And Social Services Network. (2019). Promoting the health and well-being of English-speaking Seniors in Quebec. A community model [infographic]. fs-code-orig: Community Health And Social Services Network-2019

« I don’t think that’s the way healthcare for an 85 and an 88-year-old should be done. » L’accès aux services de santé et aux services sociaux des aînés anglophones vivant hors Montréal : état de la situation [thèse de maîtrise, Université de Sherbrooke] - Ethier, Alexandra (Université de Sherbrooke, 2020)
Les aînés anglophones du Québec hors Montréal ont un accès variable aux services de santé et services sociaux (SSSS). C’est pourquoi notre recherche explore l’accès aux SSSS pour les aînés anglophones vivant hors Montréal. Spécifiquement, nous décrivons les facteurs (facilitateurs et barrières) influençant l’accès aux SSSS. Ainsi, nous avons conduit une recherche qualitative de type étude de cas unique imbriquée. Nous avons collecté les données à l’aide d’entretiens semi-dirigés audio-enregistrés, d’un questionnaire sociodémographique et d’un journal de bord. Nous avons transcrit, puis analysé thématiquement les entretiens et avons analysé les données sociodémographiques par statistiques descriptives. Les 10 aînés rencontrés nous ont permis d’identifier 11 facteurs divisés en 6 facilitateurs et 8 barrières influençant l’accès aux SSSS. Les plus signifiants sont la concordance (facilitateur) ou la non-concordance (barrière) de la langue de l’aîné avec le travailleur des SSSS, où la nonconcordance mène à des consentements aux interventions non valides. Également, le facteur présence minoritaire, c’est-à-dire la concentration de la population anglophone, affecte les opportunités sociales des aînés. Ce facteur est un facilitateur lorsque fort et une barrière, lorsque faible. Enfin, des SSSS peu « amis » des aînés anglophones, définis comme un système de SSSS complexe à naviguer lorsque la langue des aînés et leurs caractéristiques personnelles ne sont pas prises en considération, constituent également une barrière. Les résultats de cette recherche informent sur les actions à poser pour faciliter l’accès aux SSSS de ces aînés anglophones et suggèrent des améliorations bénéfiques pour l’ensemble de la population.

Strategies to access health and social services for English-speaking older adults in Quebec: A qualitative case study - Ethier, Alexandra; Carrier, Annie (Canadian Social Work Review, 2023)
Considering that French is the dominant language in Quebec, that relatively few francophone providers of health and social services are able to speak English, and that English-speaking older adults (OAs) have low levels of bilingualism, anglophone OAs are more likely than their francophone peers to face language barriers when accessing health and social services. However, little is known about the strategies English-speaking OAs put into place to overcome the difficulties encountered due to language barriers when they access these services. We therefore aimed to document the strategies used by English-speaking OAs when, due to language barriers, they faced difficulties in accessing health and social services. We conducted a qualitative case study with ten English-speaking OAs in the Eastern Townships in Quebec. Through interviews and document reviews, we collected data which we then analyzed thematically. We identified seven strategies used by English-speaking OAs: investigating for health- and access-related information in English, creating their own services, entering the health and social services system offered in French, entering the health and social services system with help from others, putting the responsibility of overcoming the language barrier on the provider, splitting that responsibility, and taking on the responsibility. Our results highlight a potential burden associated with the involvement of the English-speaking community in enabling English-speaking OAs to access health and social services. Keywords: access, health services, social services, official language minority, language barriers, strategies

Protocole d’évaluation de la sécurité à domicile (PESAD) : version francophone du SAFER-HOME v.3 - Hébert, Michèle; Brasset-Latulippe, Anne; Bourgault-Côté, Sylvianne; Meilleur, Valérie; Chiu, Teresa (Francophonies d'Amérique, 2009)
Les intervenants de la santé sont appelés à se prononcer sur la sécurité des aînés vivant à domicile et ils ont, à cet effet, très peu d’outils francophones à leur disposition. Le Protocole d’évaluation de la sécurité à domicile (PESAD) est issu de la traduction et de la validation transculturelle du SAFER-HOME. Le processus de validation et l’étude de la fidélité des résultats ont mis en lumière un outil intéressant et possédant de bonnes qualités métrologiques. Il permet aux intervenants francophones d’obtenir des résultats d’évaluation complets et rigoureux relativement à la sécurité à domicile des aînés francophones.

Comprendre l’expérience des soins de longue durée des minorités de langue officielle au Canada : état des lieux - Hsu, Amy. T.; Ménard, Alixe; Scott, Mary (Université d'Ottawa et Institut de recherche Bruyère, 2022)
fs-ref-orig: Hsu, A. T., Ménard, A. et Scott, M. (2022). Comprendre l’expérience des soins de longue durée des minorités de langue officielle au Canada : état des lieux. Université d'Ottawa et Institut de recherche Bruyère. fs-code-orig: Hsu-2022a

Understanding the long-term care experience of official language minorities in Canada: An environmental scan - Hsu, Amy; Ménard, Alixe; Scott, Mary (Bruyère Research Institut, 2022)
fs-ref-orig: Hsu, A. T., Ménard, A., & Scott, M. (2022). Understanding the long-term care experience of official language minorities in Canada: An environmental scan. Bruyère Research Institut. fs-code-orig: Hsu-2022b

Promoting the health and well-being of English-speaking seniors in Quebec. A community model - Kueber, Rusell (Community Health and Social Services Network, 2019)

Promotion de la santé et du bien-être des aînés d’expression anglaise du Québec : un modèle communautaire - Kueber, Russell (Réseau communautaire de santé et de services sociaux, 2019)

Comprendre l'expérience des soins de longue durée des minorités de langue officielle au Canada : une analyse de l'environnement | Understanding the long-term care experience of official language minorities in Canada: An environmental scan - Ménard, Alixe; Scott, Mary; Hsu, Amy T. (2022)
fs-ref-orig: Ménard, A., Scott, M. et Hsu, A. T. (2022). Comprendre l'expérience des soins de longue durée des minorités de langue officielle au Canada : une analyse de l'environnement | Understanding the long-term care experience of official language minorities in Canada: An environmental scan. Institut de recherche Bruyère. fs-code-orig: Ménard-2022

Social exclusion among official language minority older adults: A rapid review of the literature in Canada, Finland and Wales - Nyqvist, Fredica; Häkkinen, Emilia; Renaud, Alexandre; Bouchard, Louise; Prys, Cynog (Journal of Cross-Cultural Gerontology, 2021)
It has been suggested that older adults from minority linguistic and ethnic communities face higher risks of being socially excluded. The aim of this review was, therefore, to explore and review social exclusion studies conducted among official language minority older adults in three countries, namely Canada, Finland and Wales. A rapid review approach was used to review scientific literature in line with six social exclusion domains. The literature searches were made in Finnish, Swedish, English, French and Welsh and were restricted to research published within the timeline of 2001 – September 2019 and yielded 42 articles. The included studies were categorized into three different domains: socioeconomic influences, social participation and societal conditions. Converging and diverging patterns of social exclusion in old age were identified between the linguistic minorities. Linguistic barriers regarding access to health care and receiving health information were common across the three linguistic contexts, whereas exclusion from social participation was noticed amongst the linguistic minorities in Canada and Wales. Some connections between belonging to a linguistic minority and being exposed to a lower socioeconomic status and higher poverty risk were made, however, these findings were not robust across all three countries. The findings indicated that experiences of exclusion could be considered fairly common among linguistic minority older adults. We conclude that the research evidence presented in the review sheds light on issues of social inequality in old age between linguistic majorities and minorities, thus identifying important aspects of social exclusion to guide future research as well as policy and practice.

Promotion de la santé et du bien-être des aînés d'expression anglaise du Québec. Un modèle communautaire( infographie) - Réseau communautaire de santé et de services sociaux/Community Health and Social Services Network (2019)
fs-ref-orig: Réseau communautaire de santé et de services sociaux. (2019). Promotion de la santé et du bien-être des aînés d'expression anglaise du Québec. Un modèle communautaire [infographie]. fs-code-orig: Réseau communautaire de santé et de services sociaux-2019

Évaluation des services communautaires pour les aînées et aînés d’expression anglaise de Gaspésie-îles-de-la-Madeleine - Richardson, Mary (2019)
fs-ref-orig: Richardson, M. (2019). Évaluation des services communautaires pour les aînées et aînés d’expression anglaise de Gaspésie-îles-de-la-Madeleine. fs-code-orig: Richardson-2019

Prolonged Impact of the COVID-19 Pandemic on the Well-being and Roles of Family/Friend Caregivers of Older Adults Living at Home in Canadian Official Language Minority or Majority Communities - Savard, Jacinthe; Savard, Sébastien; Duong, Patrick; Hatungimana, Nelly Oriane; Benoit, Josée; De Moissac, Danielle; Dupuis-Blanchard, Suzanne; Robitaille, Annie (Canadian Journal on Aging / La Revue canadienne du vieillissement, 2026)

Pratique # 11 : The Information and Support Guide for Caregivers (Québec) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)
fs-ref-orig: Savard, J., Savard, S., van Kemenade, S., Benoît, J., Buhay, C., Youbi, S., et Kubina, L.A. (2021). Pratique # 11 : The Information and Support Guide for Caregivers (Québec). Dans : GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire. https:// www.grefops.ca/repertoire_pratiques_novatrices.html fs-code-orig: Savard-2021e

Pratique # 15 : Le volet « santé et services sociaux » de l’Association des Townshippers (Québec) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2019)

Directory of innovative practices in health and social services in official language minority contexts - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann; Dagnogo, Djenaba Sarah; Michel, Jean Nephetaly

Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann; Dagnogo, Djenaba Sarah; Michel, Jean Nephetaly

Access to health care services: East-End Montreal (Quebec) English-speaking elderly experience [master's thesis, McGill University] - Thomas, Rosemary Hellen. (2008)